The potential reuse of drinking water treatment sludge for organics removal and disinfection by-products formation control. Issue 3 (June 2022) - Khedher, Mahmoud; Awad, John; Donner, Erica; Drigo, Barbara; Fabris, Rolando; Harris, Martin; Braun, Kalan; Chow, Christopher W.K.
Abstract: Insufficient dissolved organic matter removal results in higher residual organics (measured as dissolved organic carbon, DOC) in the treated water which can act as precursors for disinfection by-products (DBPs) and consequently increases the potential for health risk. This study aims to use drinking water treatment sludge (DWTS) as a coagulant-aid to improve the DOC removal efficiency. The effect of various DWTS doses (between 0.5 and 3 g/L) on the coagulation performance (by alum) to treat natural surface water that has relatively low turbidity and high DOC at optimum pH ( 6) was examined using standard jar tests procedure. Although addition of DWTS at doses lower than 1.5 g/L improved the DOC removal efficiency (by 4% and 12% at DWTS dose of 0.5 and 1.0 g/L, respectively), the turbidity levels increased. In comparison to optimum dose of alum without DWTS, the addition of DWTS at 3 g/L led to reduce the alum dose to 50% to achieve similar removal efficiency of organics (70% DOC removal). Further, addition of DWTS improved the floc's characteristics (achieve larger flocs and rapid growth rate; measured by photometric dispersion analyser, PDA) and settling rate significantly, and the produced sludge volume decreased by 50% compared to the figure with no DWTS addition. Trihalomethane formation potential (THMFP) was also reduced (up to ∼ 30%) when DWTS used. The results indicate that DWTS reuse as a coagulant-aid has the potential to reduce DOC and control DBPs formation when the organic loads require high coagulant dose exceeding the WTP design limits. Graphical Abstract: ga1 Highlights: Drinking water treatment sludge (DWTS) used as a coagulant-aid. DWTS improved organics removal effectively and reduced the required alum dose. Floc settling ability enhanced greatly by DWTS addition and produced less sludge volume. DWTS improved the removal of humic substances with molecular weight in the range of 1–3 kDa. DWTS decreased the trihalomethanes formation potential (THMFP).